Elaborando uma ética queer - Souza, Luísa do Amaral (2022)
The purpose of this work is to establish a queer ethics in dialogue with queer theory. This effort has consisted in elaborating a non-foundationalist, non-prescriptive and anti-assimilationist ethics inspired in particular by the essay Colleen Lamos’ essay The ethics of queer theory and the ethical perspective of Gilles Deleuze. This initial result was confronted by many authors, moments and debates that marked queer theory in academia. This research aims to fill an important gap in queer theory produzed in academic institutions throughout the world